Comparing the Perceptions of Operating Room Technicians and Nurses Regarding Futile Care: A Cross-Sectional Study - Mohammad Torabi; Parisa Hajilo; Roghayeh Khabiri Nemati; Edris Kakemam; Roya Ahmadi Niya Tabesh (Taṣvīr-i salāmat, 2022)
Background. The growing trend of useless care might lead to negative consequences for patients, staff, and the organization. The employees who care for patients in their last stages of life for a long time might not tend to pay enough attention to the patients' pain. As a result, the quality of care services might be negatively affected. This study aimed to compare the perceptions of operating room technicians and nurses regarding futile care in the selected hospitals in Hamadan province, Iran from October to December. Methods. Using available sampling method, the present descriptive cross-sectional study was performed on 200 health care workers (114 nurses and 86 operating room technicians). Data collection tools included a two-part demographic information questionnaire and the perception of futile care designed based on the Corley’s Moral Distress Questionnaire. The questionnaires were distributed in person and electronically. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) software version 26. We used frequency, mean, and standard deviation for descriptive statistics and independent t-test and analysis of variance (ANOVA) for analytical statistics. Results. The mean score of nurses' perceptions regarding futile care was significantly higher (16.53±6.18) than that of operating room technicians. While the nurses' perceptions of futile care in both dimensions of intensity (66.71±13.72) and repetition (60.03 13 13.72) were at a high level, the perceptions operating room technicians in both dimensions of intensity (50.19±18.90) and repetition (52.43±18.8) were at an average level. Conclusion. Nurses seem to have a relatively better understanding of futile care compared to operating room technicians. This is probably due to frequent contacts with patients overlooking death, as well as direct contacts with their family and relatives. In this regard, it is essential to develop guidelines in Iran delimiting the standards for the staff’s provision of futile care.